Pengaruh Sistem Informasi Akuntansi Dan Integritas Terhadap Kinerja Karyawan Pada RSUD SMC Tasikmalaya - Cepi Juniar Prayoga; Fithri Sri Mulyani; Susi Mulyati (Politeknik Negeri Jember, 2021)
This study aims to examine the effect of accounting information systems and integrity on employee performance at SMC Tasikmalaya Hospital. The populations in this study were employees of the SMC Tasikmalaya Hospital as many as 491 people. The sampling technique used stratified random sampling. The data used is primary data obtained directly from respondents using a questionnaire. The data analysis technique uses multiple linear regressions. The results of this study indicate that the accounting information system partially affects employee performance. Integrity partially affects employee performance. Meanwhile, simultaneously accounting information system and integrity affect employee performance.